2015
DOI: 10.1002/smll.201501782
|View full text |Cite
|
Sign up to set email alerts
|

Suspending DNA Origami Between Four Gold Nanodots

Abstract: Rectangular DNA origami functionalized with thiols in each of the four corners immobilizes by self-assembly between lithographically patterned gold nanodots on a silicon oxide surface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Pearson et al reported a similar strategy to align DNA origami on a gold island, which was patterned with block copolymer . Later on, Morales et al further demonstrated that rectangular DNA origami structures could be suspended on four gold dots …”
Section: Applications Of Dna Origamimentioning
confidence: 99%
See 1 more Smart Citation
“…Pearson et al reported a similar strategy to align DNA origami on a gold island, which was patterned with block copolymer . Later on, Morales et al further demonstrated that rectangular DNA origami structures could be suspended on four gold dots …”
Section: Applications Of Dna Origamimentioning
confidence: 99%
“…510 Later on, Morales et al further demonstrated that rectangular DNA origami structures could be suspended on four gold dots. 511 To control the position and orientation of the DNA origami structures on the substrate surface, Kershner et al developed an electron-beam lithography and dry oxidative etching process. This new process helped to create DNA origami-shaped binding sites on SiO 2 to direct the DNA origami positions and orientations with a high selectivity and a proper orientation (Figure 26A).…”
Section: Bioanalysis With Dna Origamimentioning
confidence: 99%
“…This was for instance used by Fan and co-workers for binding a DNA tetrahedron to a gold surface with a specific face of the structure attached to the surface. 534 The gold−thiol interaction was also used for bridging gold islands with DNA origami nanotubes, 535 for trapping rectangular DNA origami with thiol-modified corners between gold islands on a SiO 2surface, 536 and for immobilization of origami using dielectrophoretic trapping between gold electrodes. 537,538 Rothemund and co-workers have further devised a methodology for covalent immobilization of DNA origami on Si/SiO 2 surfaces.…”
Section: Covalent Interactionsmentioning
confidence: 99%
“…Approaches which fix the ends of linear nanostructures on metal bars or dots (18,19,21), or align them to chemical stripes (16), add arbitrary control of position and in-plane rotation, but still cannot distinguish the orientations in Fig. 1, D to G. Nor can methods which fix the corners of rectangles (22). Here we show that absolute orientation can be achieved by DOP with suitably asymmetric DNA origami shapes, and demonstrate two applications in which absolute and arbitrary orientation work together to optimize or integrate optical devices.…”
mentioning
confidence: 99%
“…(F) Lithographic patterning of gold dots allows linear DNA structures terminated with thiols to be arbitrarily oriented (19,21) similar work on block copolymers (20) compromises arbitrary x, y, θ control for potential scalability. (G) Extension of the gold-dot/thiol approach to 2D nanostructures (rectangles) allows orientational freedom to be limited to just four degenerate orientations (22). (H) DNA origami placement of equilateral triangles still leaves six degenerate orientations, and orientational fidelity is relatively coarse, allowing only four rotations to be distinguished (24)(25)(26).…”
mentioning
confidence: 99%